How to catch a prince - Hauck, Rachel, 1960- (Hauck, Rachel, 1960- Royal wedding novel, 2015)
"Prince Stephen came to America to escape responsibility. But what he found complicates his life more than ever. Corina Del Rey is happy with her life in Melbourne, Florida. She spends her days engrossed in her career as a journalist and has her sights set on climbing the corporate ladder -- if for no other reason, to distract herself from her dissolving family. But when she is confronted with the past she fought so hard to put behind her, she struggles to make sense of her future. Prince Stephen of Brighton Kingdom has moved on since the tragic death of his buddies in Afghanistan. A star professional rugby player, he has no intention of looking over his shoulder at what could've been. But when a notice arrives in the mail requiring his and his wife's appearance before the courts to dissolve their marriage, he must deal with the questions rumbling around in his heart. He thought his marriage had been annulled long ago, but his memories of Corina Del Rey remain close. Does he still love her? Can he even find her? Above all, can he tell her the truth about that fateful night in Afghanistan seven years ago? If he does, he might really lose her forever"--